(3GdcdjGJ aj GdWHs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3bGd GdTjN GdQFjS CeG ENJjGQ cjajI GdOhGA Ydi GdGWdGb aEfgG jgJOi GdjgG HGdhbha Ydi fhY GdeQV s
(3BNQgG (B:s
(3GdJhGHd gi GdGTjGA GdJi jWHN ai GbOQ eKd GdcRHQI hGdcehf hGdfYfGY hGdTHJ Je GdHGH s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGfjI hGdYTQhfs
(3HBNQgG ahGFOs
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(568) s
Keywords: (3GdWHs